Estimation of platelet distribution width in type 2 diabetic male subjects (Bangladesh Medical Journal, 2017)
The patient with diabetes mellitus (DM) and its complication is increasing in our country and all over the world. Altered platelet morphology and function have been reported in patient with DM. Platelet indices act as a newly emerging and independent risk marker for atherothrombosis and cardiovascular diseases. The present study was carried out to assess Activated Partial Thromboplastin Time in subjects with type 2 diabetes mellitus. It was a cross sectional study and conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2013 to June 2014. A total number of 200 adult male subjects were selected with age ranging from 40 to 60 years. Among them, 100 type 2 diabetic subjects were included in the study group (Group B) and 100 healthy subjects were considered as controls (Group A) for comparison. The subjects were selected from BIRDEM, Dhaka and also by personal contact from different areas of Dhaka city on the basis of exclusion and inclusion criteria. Platelet distribution width was estimated in the Department of Hematology BIRDEM, Dhaka. For statistical analysis unpaired Students t test was performed. In this study, platelet distribution width was significantly (P